A novel pretreatment method combining sealing technique with direct injection technique applied for improving biosafety. (January 2017) - Wang, Xinyu; Gao, Jing-lin; Du, Chaohui; An, Jing; Li, MengJiao; Ma, Haiyan; Zhang, Lina; Jiang, Ye
Aim: People today have a stronger interest in the risk of biosafety in clinical bioanalysis. A safe, simple, effective method of preparation is needed urgently.Methodology/results: To improve biosafety of clinical analysis, we used antiviral drugs of adefovir and tenofovir as model drugs and developed a safe pretreatment method combining sealing technique with direct injection technique. The inter- and intraday precision (RSD %) of the method were <4%, and the extraction recoveries ranged from 99.4 to 100.7%. Meanwhile, the results showed that standard solution could be used to prepare calibration curve instead of spiking plasma, acquiring more accuracy result.Conclusion/discussion: Compared with traditional methods, the novel method not only improved biosecurity of the pretreatment method significantly, but also achieved several advantages including higher precision, favorable sensitivity and satisfactory recovery. With these highly practical and desirable characteristics, the novel method may become a feasible platform in bioanalysis.